Mechanisms of Atlantic Meridional Overturning Circulation variability simulated by the NEMO model - V. N. Stepanov; K. Haines (Ocean Science, 2014)
We have investigated mechanisms for the Atlantic Meridional Overturning Circulation (AMOC) variability at 26.5° N (other than the Ekman component) that can be related to external forcings, in particular wind variability. Resolution dependence is studied using identical experiments with 1° and 1/4° NEMO model runs over 1960–2010. The analysis shows that much of the variability in the AMOC at 26° N can be related to the wind strength over the North Atlantic, through mechanisms lagged on different timescales. At ~ 1-year lag the January–June difference of mean sea level pressure between high and mid-latitudes in the North Atlantic explains 35–50% of the interannual AMOC variability (with negative correlation between wind strength and AMOC). At longer lead timescales ~ 4 years, strong (weak) winds over the northern North Atlantic (specifically linked to the NAO index) are followed by higher (lower) AMOC transport, but this mechanism only works in the 1/4° model. Analysis of the density correlations suggests an increase (decrease) in deep water formation in the North Atlantic subpolar gyre to be the cause. Therefore another 30% of the AMOC variability at 26° N can be related to density changes in the top 1000 m in the Labrador and Irminger seas occurring ~ 4 years earlier.